Application of a preventive training program implementation framework to youth soccer and basketball organizations - Root, H. J.; Frank, B. S.; Denegar, C. R.; Casa, D. J.; Gregorio, D. I.; Mazerolle, S. M.; DiStefano, L. J. (Journal of Athletic Training, 2019)
Context Preventive training programs (PTPs) can reduce injury rates and improve neuromuscular control and sport performance. However, PTPs must be implemented correctly and consistently over time for athletes to benefit. Coaches represent the best long-term option for implementing PTPs. Youth athletes are at the optimal age for developing good habits before maturation. Although frameworks have been proposed to guide implementation efforts, little is known regarding the feasibility and real-world context of PTP implementation at the youth sport level.